Fundamentals of inertial navigation systems and aiding - Braasch, Michael (Institution of Engineering and Technology, 2022)
The aim of this book is to provide an advanced introduction to inertial data processing (determination of attitude, velocity and position) along with design architectures and algorithms used to aid the inertial navigation system (INS). The emphasis is on the high-end sensors and systems used in aerospace applications (known as 'navigation grade' or 'nav grade').
Keywords: Inertial navigation systems.; elektronické knihy; electronic books